Abbreviated MRI Protocols in Breast Cancer Diagnostics. Issue 3 (16th October 2018) - Deike‐Hofmann, Katerina; Koenig, Franziska; Paech, Daniel; Dreher, Constantin; Delorme, Stefan; Schlemmer, Heinz‐Peter; Bickelhaupt, Sebastian
Abstract : Oncologic imaging focused on the detection of breast cancer is of increasing importance, with over 1.7 million new cases detected each year worldwide. MRI of the breast has been described to be one of the most sensitive imaging modalities in breast cancer detection; however, clinical use is limited due to high costs. In the past, the objective and clinical routine of oncologic imaging was to provide one extended imaging protocol covering all potential needs and clinical implications regardless of the specific clinical indication or question. Future protocols might be more focused according to a "keep it short and simple" approach, with a reduction of patient magnet time and a limited number of images to review. Rather than replacing conventional full‐diagnostic breast MRI protocols, these approaches aim at introducing a new thinking in oncologic imaging using a diversification of available imaging approaches targeted to the dedicated clinical needs of the individual patient. Here we review current approaches on using abbreviated protocols that aim to increase the clinical availability and use of breast MRI for improved early detection of breast cancer. Level of Evidence : 2 Technical Efficacy : Stage 3 J. Magn. Reson. Imaging 2019;49:647–658.